The evaluation of psychological state of dental students during the COVID-19 pandemic - Yildirim, Tuba Talo; Atas, Osman (Sociedade Brasileira de Pesquisa Odontologica, 2021)
The purpose of the present study was to assess anxiety among a sample of dentistry students during the COVID-19 pandemic. A total of 355 dentistry students (165 males and 190 females) completed the Health Anxiety Inventory (HAI), Beck Anxiety Inventory (BAI), State-Trait Anxiety Inventory-I (STAI-I), and State-Trait Anxiety Inventory II (STAI-II) questionnaires. and evaluations of HAI, BAI, STAI-I, and STAI-II were based on sex, dental school year, smoking habit, and lifestyle. Female students had higher HAI and BAI scores than male students (p = 0.009 and p = 0.001, respectively). Statistically significant differences in HAI scores existed between preclinical and clinical students (p = 0.048). The only statistical significant differences detected in STAI-I scores involved students with an extended family when compared to students without an extended family (p = 0.039). The HAI scores of students who had close contact were significantly higher than students who had no contact (p = 0.047). There were significant correlations between the four scales (p < 0.05). During the COVID-19 pandemic [was under control in Turkey?], the HAI scores were higher in female, clinical students and students who lived with an extended family.
Keywords: COVID-19; Students; Dental; Psychology; Fear